Analysis of marketing strategy at JeKo resaturant - Putra, Ridho Maulana; Nahor, Mian Ivany Banjar; Suastika , I Kadek Dwi; Tinu, Maria Mayasari; Indah, Mawar; Ardhika, Ni Kadek Rhiska Lesthari; Sananta, I Kadek Bagus Pramoedia (Journal of Commerce, Management, and Tourism Studies, 2024)
This research aims to find out how marketing strategy is implemented at JeKo. JeKo is classified as a restaurant, but the term "restaurant" is not implied directly in the name. JeKo serves food and beverages for customers but has different ways of managing it. It is different from the other restaurants. It is located at Jalan Lettu Wayan Sutha II, Batuan, Sukawati, Gianyar, Bali. Data is collected by observation, documentation, and interviews. This research finds that JeKo has already applied marketing strategies in some aspects of marketing, especially to attract and maintain its customers.